Utilizing Anadara granosa Shells and PVA for Porous Hydroxyapatite Synthesis - Anggresani, Lia; Nurmelinda, Nurmelinda; Yulianis, Yulianis; Lee Wah Lim (Indonesian Journal of Chemical Engineering, 2023)
The majority of the inorganic material that makes up teeth and bones is called hydroxyapatite (Ca10(PO4)6(OH)2), and it is produced by isolating calcium oxide (CaO) from the high calcium carbonate content of anadara granosa shells, which is over 98%. The porous HAp is the type of hydroxyapatite that can be used for bone repair. The aim of this work is to use the polymer polyvinyl alcohol to synthesis porous hydroxyapatite from anadara granosa shell. The anadara granosa powder (AGP) was furnaced for 3 hour at 800oC. CaO powder was produced. Then, the CaO powder was treated with (NH4)2HPO4 at a mol Ca/P 1.67 to obtained the HAp. Then, HAp is combined with a PVA polymer at a 10:1 ratio. Compressive strength tests, FTIR, SEM, and XRD are carried out. The compressive strength resulted for HAp and porous HAp were14.58 and 50.43 Mpa., respectively. The results indicated that PVA achieved a good compressive strength with Hydroxyapatite – Anadara granosa shell.